Estrogen Induces Metastatic Potential of Papillary Thyroid Cancer Cells through Estrogen Receptor α and β. (10th October 2013) - Dong, Wenwu; Zhang, Hao; Li, Jing; Guan, Haixia; He, Liang; Wang, Zhihong; Shan, Zhongyan; Teng, Weiping
Abstract : Estradiol (E2) promotes metastatic propensity. However, the detailed mechanism remains largely unknown. E-cadherin, vimentin, and MMP-9 play a dominant role in the metastatic process. We aimed to investigate the effects of E2 on metastatic potential of PTC cell line BCPAP and on E-cadherin, vimentin, and MMP-9 protein expression. PTC cell line BCPAP was evaluated for the presence of estrogen receptor (ER) by western blot analysis. The effects of E2, PPT (a potent ER α -selective agonist), and DPN (a potent ER β -selective agonist) on modulation of metastatic phenotype were determined by using in vitro scratch wound assay and invasion assay. In addition, the effects on E-cadherin, vimentin, and matrix metalloproteinase-9 (MMP-9) protein expression were evaluated by Western blot analysis. We found that BCPAP cells expressed ER α and ER β . E2 and PPT enhanced, but DPN inhibited, the migration and invasion of BCPAP cells in an in vitro experimental model system that is modulated by E-cadherin, vimentin, and MMP-9. These findings indicate that E2 induces the metastatic potential of BCPAP cells through ER α and ER β . The two ER subtypes play differential roles in modulation of BCPAP cell metastasis and the related molecule expressions including E-cadherin, vimentin, and MMP-9.